Isolation, Identification of Secondary Metabolites and Anti Bacterial Property of Memecylon Edule Leaves Extract - M. M., Yusoff; Kuppusamy, Palaniselvam; Raj, R. S. David Paul; Natanamurugaraj, Govindan (SESSO Periodicals, 2012)
The present study aims to determine the preliminary phytochemical screening, revealed the presence of alkaloids, flavanoids, saponins, glycosides and oil compounds using FT-IR and GC-MS analyses. The methanolic extract of Memecylon edule to check the antibacterial activity for the maximum inhibitory concentration against E.coli, (15mm) and Staphylococcus aureus (14mm) with minimum inhibitory concentration 6.25μg/ml. The minimum inhibitory growth against Pseudomonos auroginosa and Klebsella pneumoniae (12mm, 1 1mm) respectively. The result of GC-MS study was confirmed the squalene, palmitic acid, fatty acid and also related functional group were identified using FT-IR spectra. Hence in this research work suggests the traditional plant Memecylon edule contain various phytochemical compounds. It represents effect of pathogenic bacteria to inhibit the growth response.